Pengembangan Paham Moderasi Beragama di Pondok Pesantren Al-Ikhlas Ujung Kabupaten Bone - Arake, Lukman; Makkarateng, Ma'adul Yaqien (IAIN Bone, 2023)
Moderate attitudes in understanding and practicing religious teachings are highly necessary to be instilled in every Muslim, as they lead to the avoidance of conflicts with people from different beliefs. Islamic teachings about moderation in worship, as written in the Qur'an and Hadith, imply the principles of justice and balance in practicing religion. These principles are the essence of Islamic teachings that emphasize the